A Historical Review on Antibiotic Resistance of Foodborne Campylobacter - Yang, Yichao; Feye, Kristina M.; Shi, Zhaohao; Pavlidis, Hilary O.; Kogut, Michael; J. Ashworth, Amanda; Ricke, Steven C. (Frontiers in Microbiology, 2019)
Campylobacter is one of the most commonly reported foodborne human bacterial gastrointestinal pathogens. Campylobacter is the etiological agent of campylobacteriosis, which is generally a self-limited illness and therefore does not necessitate treatment. However, when immunocompromised status and other co-morbidities necessitate antimicrobial treatment. For clinical treatment of campylobacteriosis, macrolides and fluoroquinolones are the as the drug choices. However, the resistance of Campylobacter to these clinically important antibiotics has been reported. This discovery has lead the CDC to acknowledge the rise in antibiotic-resistant and multiple antibiotic-resistant campylobacteriosis as serious threat to human health the United States. Because of the transmission between poultry and humans, the poultry industry must now allocate resources to address the problem by reducing Campylobacter as well as antimicrobial use which may reduce resistance. This review will focus on the incidence of antibiotic resistant Campylobacter in poultry, the clinical consequences of this resistance, and the mechanisms of antibiotic resistance associated with Campylobacter.